Life cycle assessment approach of waste management for ship operation - Bilgili, L.; Celebi, U. B. (CRC PRESS-TAYLOR & FRANCIS GROUP, 2013)
Ships have an indispensable role in trading and transportation. Due to the growth of population and the new demands of the growing economies, the need for shipping is increasing. Besides shipping causes a considerable problem for human and environmental issues, increasing amount of shipping activity will constitute a greater danger by more energy consumption and harmful emissions to air and water. Ship operation is the most emission-produced phase of a ship's life cycle. Due to the spillages, accidents, gaseous form of emissions as a result of main and auxiliary engines' activities, and discharges to water (solid and liquid wastes), ship operation phase has a considerable role of the environmental impact of a ship. Life Cycle Assessment (LCA) is a totally new method that is used by universities, companies and even local and international legislators. LCA aims to reduce, minimize and if possible, initialize the consumed energy, harmful emissions and discharges in a whole life cycle of a product. LCA consists all of the phases from the raw material to disposal/recycling. In this paper, LCA method is presented and the method's effects on reducing the emissions and discharges during ship operation. Waste management modeling is highlighted.
Keywords: BALLAST; EMISSIONS; Engineering; Environmental Sciences & Ecology; Materials Science